TRANSITIONING FROM FEMININE PERSPECTIVE TO MASCULINITY - AN EXAMINATION OF GENDER IDENTITY AND EXPRESSION IN CHINESE WOMEN DIRECTOR MA LIWEN’S WORK - Wenyu Jiang; Wan Aida Wan Yahaya (Journal of Islamic, Social, Economics and Development, 2024)
The discussions surrounding the works of contemporary female filmmakers have sparked a heated debate in China. Ma Liwen recognized as one of the most pioneering female filmmakers in the new era of Chinese cinema, has become a controversial figure in this discourse. Utilizing cultural studies and feminism theories, this paper seeks to analyze the director's perspectives on gender in the context of two films, namely ‘Gone Is the One Who Held Me Dearest in the World’ (2002) and ‘Desires of the Heart’ (2008). I selected these two films for examination because they are highly representative and signify a transition where female filmmakers are moving from low-budget independent filmmaking to mainstream commercial cinema. This transition is still relevant today.